2020
DOI: 10.1038/s42003-020-01374-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid poxvirus engineering using CRISPR/Cas9 as a selection tool

Abstract: In standard uses of CRISPR/Cas9 technology, the cutting of genomes and their efficient repair are considered to go hand-in-hand to achieve desired genetic changes. This includes the current approach for engineering genomes of large dsDNA viruses. However, for poxviruses we show that Cas9-guide RNA complexes cut viral genomes soon after their entry into cells, but repair of these breaks is inefficient. As a result, Cas9 targeting makes only modest, if any, improvements to basal rates of homologous recombination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 63 publications
0
40
0
Order By: Relevance
“…Genetic manipulation of giant viruses has been a neglected topic of research since their discovery despite the immense richness in genes with unknown functions encoded by their genome. Homology recombination has been used as a powerful tool to modify the genome of other viruses (Gowripalan et al, 2020), and we show here that it can be efficiently utilized for genetic manipulation of MV. Moreover, the essentiality of genes that encode MV histones, like mel_369 and mel_368, can be overcome by trans-complementation, introducing ectopic copies of the gene in the amoeba genome.…”
Section: Discussionmentioning
confidence: 81%
“…Genetic manipulation of giant viruses has been a neglected topic of research since their discovery despite the immense richness in genes with unknown functions encoded by their genome. Homology recombination has been used as a powerful tool to modify the genome of other viruses (Gowripalan et al, 2020), and we show here that it can be efficiently utilized for genetic manipulation of MV. Moreover, the essentiality of genes that encode MV histones, like mel_369 and mel_368, can be overcome by trans-complementation, introducing ectopic copies of the gene in the amoeba genome.…”
Section: Discussionmentioning
confidence: 81%
“…Selection of poxvirus recombinants by homologous recombination is a long and laborious process and so alternatives are needed. Recent improvements have included the synthesis of horsepox virus from chemically synthesized DNA, which could be used to make recombinants [ 52 ], and the use of CRISPR/Cas9 technology to target the parent poxvirus genome [ 53 ]. Both these approaches are relatively expensive.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these workflows still required the use of selectable markers and multiple rounds of plaque purification. A more recent study demonstrated that Cas9 could rapidly and efficiently cleave vDNA in cells, but found that cleavage reduced viral replication and multiplication while having no stimulating effect on genome repair through homologous recombination [13]. This may be the case because (i) the cytoplasmic vDNA cannot be repaired by cellular HDR, which requires components that are localized to the nucleus; and (ii) efficient cleavage of vDNA by Cas9 soon after viral entry may inhibit VACV DNA replication, thereby also inhibiting homologous recombination, to which it is coupled.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CRISPR/Cas9 engineering [10] has been employed in attempts to streamline the rVACV rescue process [11][12][13][14][15]. Yuan and co-workers [11] introduced Streptococcus pyogenes Cas9 and vDNA-specific single-guide RNAs (sgRNAs) into cells to cleave the vDNA from infecting VACVs and enhance its homologous recombination with a transfected transfer plasmid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation